Assessing Undergrowth Biomass Carbon Variability Under Different Strata in Temperate Himalayan Region - Wani, Akhlaq A.; Joshi, P. K.; Singh, Ombir; Gatoo, Asif A.; Singh, Amarjeet; Mir, Rafiq A.; Khaki, Bilal A.; Murtaza, Shah (Indian Forester, 2016)
Realizing the importance of carbon monitoring and reporting in climate change, it becomes imperative to assess the contribution of less significant but equally important forest carbon sub-pool of shrubs and herbs in mitigating the atmospheric carbon. The present study was conducted to calculate the strata wise biomass carbon of undergrowth (herbs and shrubs) in the coniferous forests of Western Himalayan region. Quadrates of 0.1 ha were laid in six forest types and within these plots, shrub plots (5m X 5m) were laid at the opposite corners. Herb plots (herbs including freshly fallen litter) (1m X 1m) m were laid inside the shrub plots at the opposite corners for undergrowth measurements. Shrub and herb measurements were taken by total harvest method and sub-samples weighing 200 g packed tight were transferred to the laboratory and oven dried at 65 Â± 5 Â°C to a constant weight. The estimated biomass from these plots was extrapolated to one ha. The total herb biomass hence calculated was converted into carbon equivalent using a factor of 0.50. The entire results were subjected to statistical tools using analysis of variance (ANOVA). The results revealed that shrub biomass carbon was found to be highest under Deodar (closed) strata 0.65 t ha-1 ( Â±Ïƒ 0.48) and minimum under Deodar (open) 0.17 t ha-1 ( Â± Ïƒ 0.20) with p<0.05. For herb biomass carbon the highest values were observed under Fir-Spruce (closed) 1.32 t ha-1 ( Â±Â Ïƒ 0.46) and minimum under Blue Pine (open) 0.59 t ha ( Â±Â Ïƒ 0.49) with p<0.05. The open forests were subjected to a high biotic interference as a result of uncontrolled grazing, fuel wood and fodder collection that led to the lower values for undergrowth biomass carbon. However these strata were found to have a promising potential to fix atmospheric carbon into herbs and shrubs once the conservative interventions are brought into practice.